Understanding Factors Influencing Repurchase Intention of Generation Y Online Shopping - Amran Harun; Mohd Nazir, Annis Najwa; Abu Seman, Noor Aslinda; Mohamad, Arifha; Mohammad Zabri, Shafie (JBS Nexus, 2024)
This research aims to study the relationship between perceived ease of use, perceived usefulness, trust, enjoyment and privacy with customer repurchase intention. Many previous researchers have validated the significant relationships between these factors and customer repurchase intention. However, there is a limited study on customer repurchase intention among Generation Y. Therefore, this study examined factors influencing customer repurchase intention in online shopping among Generation Y. A quantitative approach is adopted using a questionnaire (online and offline) as the primary instrument for data collection. A total of 382 Generation Y respondents in Batu Pahat, Johor, were chosen using mall intercept at selected malls in Batu Pahat during the weekend and an online survey through Google Documents. A multiple regression was used to analyze the relationship of variables using SPSS software version 20. This study found that perceived ease of use, usefulness, trust, enjoyment, and privacy positively and significantly influence customer repurchase intention in online shopping among Generation Y. This study provided a better understanding to researchers, industry and government on factors influencing customer repurchase intention in online shopping